Effectiveness of family health education in malaria elimination programmes: a scoping review - Misra Helma Firdaus; Sharifa Ezat Wan Puteh; Rosnah Sutan; Mohd Rizal Abdul Manaf (Malaria Journal)
Abstract Background Malaria remains a significant global health issue, with vector control strategies likes indoor residual spraying (IRS) and insecticide-treated nets (ITNs) show promise, socio-cultural and structural challenges often hinder their success. Family and community involvement, including individual adherence, household leadership, and participation by community leaders, are crucial in enhancing intervention outcomes. This review evaluates family health education's effectiveness in improving public health impact on malaria elimination programmes. Methods A systematic review was conducted using Scopus, Web of Science, and PubMed, yielding 1,121 records through a predefined Population, Exposure, Outcome (PEO)-based search strategy. The review focused on studies published between 2019 and 2024 examining malaria elimination programmes and family health education. The Population consisted of families in malaria-endemic regions, particularly rural and urban areas of sub-Saharan Africa and Southeast Asia, including households with young children and pregnant women. The Exposure was participation in malaria elimination programmes, and the Outcome was the effectiveness of family health education in enhancing awareness, knowledge, and public health outcomes. Review articles, editorials, conference papers, and proceedings were excluded. Data extraction adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines, and studies were appraised using the Mixed Methods Appraisal Tool (MMAT). Results This study examines the effectiveness of malaria health education programmes using a socio-ecological framework, focusing on individual, family, and community-level influences. Twelve studies met the inclusion criteria, exploring interventions likes IRS and ITN across diverse populations. At the individual level, educational programmes significantly enhanced malaria knowledge and prevention behaviours. Within families, health education strengthened decision-making and reinforced preventive measures. At the community level, engagement in malaria-related initiatives improved collective action, though policy barriers limited widespread implementation. The review employed various research designs, underscore the role of multi-stakeholder involvement in ensuring the effectiveness of malaria elimination programmes. Conclusion This study highlights the important of family structure in malaria elimination emphasizing maternal leadership in decision-making and health-seeking behaviours. Integrating family health education into public health strategies can enhance intervention effectiveness, improve adherence and promote long-term sustainability. Future programmes should leverage maternal influence and community engagement to strengthen malaria elimination programmes’ efforts.